Reorientation of Pancasila and Citizenship Education in Elementary Schools in the Discourse of Smart and Good Citizenship - Putri Handriyani (International Journal of Students Education, 2024)
The purpose of writing this article is to reorient Pancasila and Citizenship Education in Elementary Schools in the discourse of smart and good citizenship, examining the discourse of citizenship. The method used in this article is library research. The data collection technique is carried out by coding data. The data analysis carried out in this research was inductive, namely with two stages in the form of data reduction and presentation of document data. The results of the analysis show that the reorientation of Pancasila and Citizenship Education in Elementary Schools in the citizenship discourse is an affirmation that Pancasila and Citizenship Education is part of character education. Through this article, the researcher recommends that future researchers conduct extensive and in-depth studies regarding Pancasila and Citizenship Education in Elementary Schools.